STUDENTS’ INTEREST IN USING MOBILE BASED DICTIONARY IN ENGLISH LEARNING AT ENGLISH DEPARTMENT OF FKIP UMMY SOLOK AT 2018/2019 ACADEMIC YEAR - Marsika Sepyanda (Jurnal Akrab Juara, 2019)
This research is based on the development of technology that has brought wide impact on teaching and learning process, especially in university level. It can be seen from the use of mobile devices as learning supporting tools for the students. Due to the development, mobile phones and their applications are considered bring good benefits on language learning. One of the forms is mobile based dictionary where there are many kinds of application that can help the students in teaching and learning process. This research aimed to know about types of mobile based dictionary used interestedly by the students at English Department. It also aimed to find out the level of students’ interest in using mobile based dictionary in English. In addition, it meant to know the dominant factors that influence student's interest in using mobile based dictionary in English learning at English Department of FKIP UMMY Solok at 2018/2019 academic year. The design of this research was descriptive qualitative research. It was conducted on the students in English department of FKIP UMMY Solok who are registered on 2018/2019 academic year. Purposive sampling was used as sampling technique, where the samples were chosen because they are registered as active students on that semester. There were 21 students got a questionnaire in order to know their interest in using mobile based dictionary. The result of this research showed that there are several types of mobile based dictionary commonly used by the students. Then, it was found that the percentage of students’ interest was 75%. It means that the students’ interest in mobile based dictionary in English Department of FKIP UMMY Solok in 2018/2019 academic year can be classified into good level. Moreover, internal factors became dominant factors that influence student's interest in using mobile based dictionary in English learning at English Department of FKIP UMMY Solok at 2018/2019 academic year